Beneficial Interactive Effects Provided by an Arbuscular Mycorrhizal Fungi and Yeast on the Growth of Oenothera picensis Established on Cu Mine Tailings - Rodrigo Pérez; Yasna Tapia; Mónica Antilén; Antonieta Ruiz; Paula Pimentel; Christian Santander; Humberto Aponte; Felipe González; Pablo Cornejo (Plants, 2023)
Phytoremediation, an environmentally friendly and sustainable approach for addressing Cu-contaminated environments, remains underutilized in mine tailings. Arbuscular mycorrhizal fungi (AMF) play a vital role in reducing Cu levels in plants through various mechanisms, including glomalin stabilization, immobilization within fungal structures, and enhancing plant tolerance to oxidative stress. Yeasts also contribute to plant growth and metal tolerance by producing phytohormones, solubilizing phosphates, generating exopolysaccharides, and facilitating AMF colonization. This study aimed to assess the impact of AMF and yeast inoculation on the growth and antioxidant response of Oenothera picensis plants growing in Cu mine tailings amended with compost. Plants were either non-inoculated (NY) or inoculated with Meyerozyma guilliermondii (MG), Rhodotorula mucilaginosa (RM), or a combination of both (MIX). Plants were also inoculated with Claroideoglomus claroideum (CC), while others remained non-AMF inoculated (NM). The results indicated significantly higher shoot biomass in the MG-NM treatment, showing a 3.4-fold increase compared to the NY-NM treatment. The MG-CC treatment exhibited the most substantial increase in root biomass, reaching 5-fold that in the NY-NM treatment. Co-inoculation of AMF and yeast influenced antioxidant activity, particularly catalase and ascorbate peroxidase. Furthermore, AMF and yeast inoculation individually led to a 2-fold decrease in total phenols in the roots. Yeast inoculation notably reduced non-enzymatic antioxidant activity in the ABTS and CUPRAC assays. Both AMF and yeast inoculation promoted the production of photosynthetic pigments, further emphasizing their importance in phytoremediation programs for mine tailings.